Sistem Informasi Geografis Pemetaan Pembangunan Desa (Yayasan Kawanad, 2022)
The purpose of this study is to build a geographic information system for mapping the development of funds based on a geographic formation system that can provide information to the community about the development of funds obtained from each village and the activities in it with map visualization. The research method consists of stages; 1) Data collection, 2) Analysis of collected data, 3) Application design and design, 4) Application implementation, and 5) Testing and Evaluation. The results of the study found that; 1) The system can be used to manage the results of village development data that is carried out online properly because the data is centralized on one server and at any time it is needed it can be searched easily, and 2) The system can make it easier for the sub-district to provide information about the development of the village concerned to certain parties and the community, henceforth the data becomes very valuable data to determine the policies to be taken by management in order to improve the quality of village development.